Composição química e degradabilidade ruminal de fenos de leguminosas da caatinga - Pinto, Márcia Marcila Fernandes (Universidade Federal Rural do Semi-Árido, 2016)
Aiming to evaluate the chemical-bromatological composition and ruminal degradability of dry matter (DM), crude protein (CP) and neutral detergent fiber (NDF) of the hay of legumes Catingueira (Caesalpinia pyramidalis, Tul), Sabiá (Mimosa caesalpiniifolia Benth), Jucá (Caesalpinia ferrea Mart. ex Tul), Canafístula (Senna spectabilis var. excelsa) and Feijão-de-rola (Macroptillium lathiroydes), were used three sheep (SPRD) with rumen fistulae, kept in collective pens, daily getting the studied plants associeted with Capim canarana (Echinochloa pyramidalis). The animals underwent adjustment period of seven days. The plants were sun-dried in the sun and crunched into a 4.0 mm sieve, and the samples were incubated in the same periods of 2, 6, 12, 24, 48, 72 and 96 hours using TNT bags weight 60, the dimensions of 10 x 10 cm. It were performed analyzes the chemical-Bromatological Legume. The experimental design was a randomized block with split plots. The leguminous plants Jucá and Sabiá had presented the highest crude protein concentrations (24,00 and 12,92%) and also the higher lignin content (8.28 and 7.8%). The effective degradability of dry matter Catingueira was the highest observed among the legumes studied with 52.93 values; 45.27 and 41.55% / h (2, 5 and 8 hours), respectively. The jucá legume, has showed higher values for potential degradability (72.47%) and degradability Effective of crude protein (50.13, 39.86 and 35.62%/h) for 2, 5 and 8 hours, respectively. The Feijão-de-rola showed higher effective degradability of fiber neutral detergent 42.56; 35.51 and 31.68%/h for passage rate of 2%/h; 5% / h and 8%/h, respectively. All legumes evaluated show good potential for use in animal feed due bromatological chemical-composition and degradability rates, with the exception of thrush, which showed low degradability coefficients for all the fractions DM, CP and NDF
Chemical composition and degradability ruminal hays of leguminous plant of caatinga
Keywords: Alimentação; Microrganismos; Nordeste; Ovinos; Feeding; Microrganisms; Northeast; Sheep; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL